Tumor Vascular Morphology Undergoes Dramatic Changes during Outgrowth of B16 Melanoma While Proangiogenic Gene Expression Remains Unchanged. (4th December 2011) - Langenkamp, Elise; vom Hagen, Franziska M.; Zwiers, Peter J.; Moorlag, Henk E.; Schouten, Jan P.; Hammes, Hans-Peter; Gouw, Annette S. H.; Molema, Grietje
Abstract : In established tumors, angiogenic endothelial cells (ECs) coexist next to "quiescent" EC in matured vessels. We hypothesized that angio-gene expression of B16.F10 melanoma would differ depending on the growth stage. Unraveling the spatiotemporal nature thereof is essential for drug regimen design aimed to affect multiple neovascularization stages. We determined the angiogenic phenotype—represented by 52 angio-genes—and vascular morphology of small, intermediate, and large s.c. growing mouse B16.F10 tumors and demonstrated that expression of these genes did not differ between the different growth stages. Yet vascular morphology changed dramatically from small vessels without lumen in small to larger vessels with increased lumen size in intermediate/large tumors. Separate analysis of these vascular morphologies revealed a significant difference in α SMA expression in relation to vessel morphology, while no relation with VEGF, HIF-1 α, nor Dll4 expression levels was observed. We conclude that the tumor vasculature remains actively engaged in angiogenesis during B16.F10 melanoma outgrowth and that the major change in tumor vascular morphology does not follow molecular concepts generated in other angiogenesis models.